A new collagen scaffold for the improvement of corneal biomechanical properties in a rabbit model. (June 2021) - Andreev, Andrey Yurevich; Osidak, Egor Olegovich; Grigoriev, Timofei Evgenievich; Krasheninnikov, Sergey Vladimirovich; Zaharov, Valeriy Dmitrievich; Zaraitianc, Oleg Vadimovich; Borzenok, Sergey Anatolievich; Domogatsky, Sergey Petrovich
Abstract: Although collagen based materials are widely used in corneal tissue engineering with promising results. The usage of such materials for the improvement of corneal biomechanical properties is still unclear. In this study, we aimed to investigate a new Viscoll collagen-based membrane for the improvement of corneal biomechanical characteristics.The right eyes of 15 Chinchilla rabbits were implanted with the membrane via an intrastromal pocket, with the contralateral intact eyes as controls. At 7, 30, 90, and 180 days post-surgery, the rabbits underwent anterior segment optical coherence topography, clinical examination, and slit-lamp microscopy. Additionally, the corneal samples also underwent histological examination followed by the assessment of the biomechanical characteristics of four treated and non-treated corneas at 30, 90, and 180 days, including keratometry at 180 days, post operation. Data are presented as means ± confidence intervals with a 95% confidence level. All the operated corneas retained their transparency throughout the study. Implantation approximately doubled the central corneal thickness. Corneas became stronger by approximately 87% between 1 and 6 months after surgery (maximum fracture load, 13.3 ± 0.8 and 24.9 ± 1.4 N, respectively), and their elasticity increased by approximately 27% over the same time frame (maximum slope of the elastic region of the stress-strain curve, 11.5 ± 0.2 and 14.6 ± 1.4 N/mm respectively). We have thus proposed a new method to increase corneal thickness and strengthen the corneal tissues while preserving their transparency and demonstrated its safety and efficacy in a rabbit model over 6 months. This may be a suitable alternative to the existing corneal collagen crosslinking procedure. Highlights: A Viscoll collagen-based membrane improves corneal biomechanical properties. Viscoll increased corneal tissue thickness and strength and retained transparency. Viscoll may be a suitable alternative to corneal collagen cross-linking procedures.